Historic characteristics and mortality of patients in the Swiss Amyloidosis Registry - Brouwers, Sofie; Heimgartner, Raphael; Laptseva, Natallia; Aguzzi, Adriano; Ehl, Niklas F.; Fehr, Thomas; Hitz, Felicitas; Jung, Hans H.; Kälin, Joel; Manz, Markus G.; Müllhaupt, Beat; Ruschitzka, Frank; et al. (Swiss medical weekly, 2024)
AIMS OF THE STUDY: Systemic amyloidoses are rare protein-folding diseases with heterogeneous, often nonspecific clinical presentations. To better understand systemic amyloidoses and to apply state-of-the-art diagnostic pathways and treatment, the interdisciplinary Amyloidosis Network was founded in 2013 at University Hospital Zurich. In this respect, a registry was implemented to study the characteristics and life expectancy of patients with amyloidosis within the area covered by the network. Patient data were collected retrospectively for the period 2005–2014 and prospectively from 2015 onwards. METHODS: Patients aged 18 years or older diagnosed with any subtype of systemic amyloidosis were eligible for inclusion if they were treated in one of the four referring centres (Zurich, Chur, St Gallen, Bellinzona). Baseline data were captured at the time of diagnosis. Follow-up data were assessed half-yearly for the first two years, then annually. RESULTS: Between January 2005 and March 2020, 247 patients were screened, and 155 patients with confirmed systemic amyloidosis were included in the present analysis. The most common amyloidosis type was light-chain (49.7%, n = 77), followed by transthyretin amyloidosis (40%, n = 62) and amyloid A amyloidosis (5.2%, n = 8). Most patients (61.9%, n = 96) presented with multiorgan involvement. Nevertheless, single organ involvement was seen in all types of amyloidosis, most commonly in amyloid A amyloidosis (75%, n = 6). The median observation time of the surviving patients was calculated by the reverse Kaplan-Meier method and was 3.29 years (95% confidence interval [CI] 2.33–4.87); it was 4.87 years (95% CI 3.14–7.22) in light-chain amyloidosis patients and 1.85 years (95% CI 1.48–3.66) in transthyretin amyloidosis patients, respectively. The 1-, 3- and 5-year survival rates were 87.0% (95% CI 79.4–95.3%), 68.5% (95% CI 57.4–81.7%) and 66.0% (95% CI 54.6–79.9%) respectively for light-chain amyloidosis patients and 91.2% (95% CI 83.2–99.8%), 77.0% (95% CI 63.4–93.7%) and 50.6% (95% CI 31.8–80.3%) respectively for transthyretin amyloidosis patients. There was no significant difference between the two groups (p = 0.81). CONCLUSION: During registry set-up, a more comprehensive work-up of our patients suffering mainly from light-chain amyloidosis and transthyretin amyloidosis was implemented. Survival rates were remarkably high and similar between light-chain amyloidosis and transthyretin amyloidosis, a finding which was noted in similar historic registries of international centres. However, further studies are needed to depict morbidity and mortality as the amyloidosis landscape is changing rapidly.